2023
DOI: 10.3390/cells12040522
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in the Pathogenesis of Atherosclerosis

Abstract: A wide variety of cell populations, including both immune and endothelial cells, participate in the pathogenesis of atherosclerosis. Among these groups, macrophages deserve special attention because different populations of them can have completely different effects on atherogenesis and inflammation in atherosclerosis. In the current review, the significance of different phenotypes of macrophages in the progression or regression of atherosclerosis will be considered, including their ability to become the foam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Dyslipidemia is characterized by impaired lipid metabolism, leading to an increase in LDL cholesterol and a decrease in high-density lipoprotein cholesterol (HDL). This leads to the accumulation of LDL cholesterol in the arterial walls, where it is oxidized and taken up by macrophages to form foam cells that are involved in plaque formation [ 36 ]. In addition to these systemic risk factors, local hemodynamic disturbances contribute to the development of atherosclerotic lesions in certain arterial areas [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is characterized by impaired lipid metabolism, leading to an increase in LDL cholesterol and a decrease in high-density lipoprotein cholesterol (HDL). This leads to the accumulation of LDL cholesterol in the arterial walls, where it is oxidized and taken up by macrophages to form foam cells that are involved in plaque formation [ 36 ]. In addition to these systemic risk factors, local hemodynamic disturbances contribute to the development of atherosclerotic lesions in certain arterial areas [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of note that other studies found that both M1ϕ/M2ϕ phenotypes could markedly upregulate CD38 + CD23 + in disease, which can prime DCs and naïve T cells [ 254 ]. Moreover, it was clarified by gene protein analysis that differential M1ϕ or M2ϕ polarization could be induced in vitro with M1ϕ expressing IL-6, TLR4, CXCL9, CXCL10, and CXCL11, while M2ϕ expressed CD206, CCL17, and CCL22 (with gene markers STAT6, IRF4) [ 233 , 255 ]. This was an interesting finding, as TLR4 is historically activated by bacterial antigens, while CCL17 and CCL22 seem to be relevant as DC and Mϕ chemokines.…”
Section: Inflammatory Cells and Phagocytesmentioning
confidence: 99%
“…Macrophages can polarize to two phenotypes: M1 and M2. M1 macrophages exacerbate the inflammatory response, and M2 macrophages are involved in the resolution of inflammation [68]. In a mouse model of diabetes with atherosclerosis and hypercholesterolemia, empagliflozin decreased the proliferation of plaque-resident macrophages and reduced the size of atherosclerotic plaques [69].…”
Section: Sglt2i Attenuate Vascular Inflammationmentioning
confidence: 99%